Restorative Justice: International Trends - (:unkn) unknown (My University, 2016)
Restorative justice is a growing international movement within the fields ofjuvenile and criminal justice. It is different from conventional justice processes inthat it views crime primarily as injury (rather than primarily as lawbreaking), andthe purpose of justice as healing (rather than as punishment alone). Itemphasises accountability of offenders to make amends for their actions, andfocuses on providing assistance and services to the victims. Its objective is thesuccessful reintegration of both victim and offender as productive members ofsafe communities.